Electrochemical and optical detectors for capillary and chip separations - Xu, Xiaomi (2007)
In separations in capillaries or on chips, the most predominant detectors outside of the field of proteomics are electrochemical (EC) and optical. These detectors operate in the μM to pM range on nL peak volumes with ms time resolution. The driving forces for improvement are different for the two classes of detectors. With EC detectors, there are two limitations that the field is trying to overcome. One is the ever-present surface of the electrode which, while often advantageous for its catalytic or adsorptive properties, is also frequently responsible for changes in sensitivity over time. The other is the decoupling of the electrical systems that operate electrokinetic separations from the system operating the detector. With optical detectors, there are similarly a small number of important limitations. One is the need to bring the portability (size, weight and power requirements) of the detection system into the range of EC detectors. The other is broadening and simplifying the applications of fluorescence detection, as it almost always involves derivatization. Limitations aside, the ability to make detector electrodes and focused laser beams of the order of 1 μm in size, and the rapid time response of both detectors has vaulted capillary and chip separations to the forefront of small sample, fast, low mass-detection limit analysis.